Study on circulation control of flying wing based on Coanda effect - LIU Xiaodong; CAI Weimin; ZHANG Peiliang; WANG Yongen; HUANG Yong; GAO Lihua (Xibei Gongye Daxue Xuebao, 2022)
In recent years, it has been a hot spot to use flow control technology to generate control capability similar to mechanical rudder. Taking the flying wing configuration as the research object, based on CFD and low speed wind tunnel test, the circulation control of airfoil and wing based on Coanda effect is studied, and the parameter influence law and control effect are given. The results show that: when the rear edge of the wing is opened with the corresponding slot, the control capability of the upper-surface blowing is similar to that of the mechanical rudder; the control capacity of pitch and roll is increased with the decreasing of jet height and the increasing of air pressure ratio, the pitching and rolling capacity increases first and then decreases; the control effect of circular Coanda surface is better than elliptical Coanda surface; the pitching and rolling control effect of the optimized circulation-control scheme in Ma=0.2 is not lower than that of the mechanical rudder, the corresponding flow flux is about 0.05~0.07 kg/s.